Manajemen Inovasi Pendidikan dalam Perspektif Sekolah Efektif - Ahmad Matinul Haq; Sujarwanto Sujarwanto; Nunuk Hariyati (Jayapangus Press, 2023)
This research aims to analyze and clarify the management of educational innovation from an effective school perspective. This scientific article research method uses systematic library observation with the PRISMA (Preferred Reporting Items For Systematic Review and Meta-analysis) model by applying complete and detailed steps in carrying out library observations of journal articles. In this case, a literature search was carried out, both in the form of national literature and international literature, using the Scoopus, Emerald and Google Scholar databases. In the initial stage of the article search, 150 articles were identified, then screened and screened to produce 85 articles. Then feasibility or feasibility was carried out and produced 45 articles. Then the final stage was carried out by producing 25 articles. The result of this scientific article is that effective management of educational innovation from a school perspective is a systematic process that involves planning, implementation, evaluation and further action of school resources in realizing educational goals efficiently and effectively. Effective schools have a number of characteristics such as a consistent vision and mission, strong leadership, planned programs and curriculum, ongoing evaluation, supportive facilities, and active involvement of students, teachers, parents and the community. As well as realizing innovation in managing changes and new developments in the field of education. This is in accordance with school goals through the rational and systematic use of all school resources.